Catharanthus roseus intoxication mimicking acute cholangitis - Yoen Young Chuah; Yeong Yeh Lee; Chu-Kuang Chou; Li-Jen Chang (BMC, 2024)
Abstract Background Catharanthus roseus, a Madagascar native flowering plant, is known for its glossy leaves and vibrant flowers, and its medicinal significance due to its alkaloid compounds. As a source of vinblastine and vincristine used in chemotherapy, Catharanthus roseus is also employed in traditional medicine with its flower and stalks in dried form. Its toxicity can lead to various adverse effects. We report a case of Catharanthus roseus juice toxicity presenting as acute cholangitis, emphasizing the importance of healthcare providers obtaining detailed herbal supplement histories. Case presentation A 65-year-old woman presented with abdominal pain, fever, anorexia, and lower limb numbness. Initial diagnosis of acute cholangitis was considered, but imaging excluded common bile duct stones. Further investigation revealed a history of ingesting Catharanthus roseus juice for neck pain. Laboratory findings showed leukocytosis, elevated liver enzymes, and hyperbilirubinemia. The patient developed gastric ulcers, possibly due to alkaloids in Catharanthus roseus. No bacterial growth was noted in blood cultures. The patient recovered after discontinuing the herbal extract. Conclusions Catharanthus roseus toxicity can manifest as fever, hepatotoxicity with cholestatic jaundice, and gastric ulcers, mimicking acute cholangitis. Awareness of herbal supplement use and potential toxicities is crucial for healthcare providers to ensure prompt diagnosis and appropriate management. This case emphasizes the need for public awareness regarding the possible toxicity of therapeutic herbs and the importance of comprehensive patient histories in healthcare settings.